De novo variants in MED12 cause X-linked syndromic neurodevelopmental disorders in 18 females - Polla, D. L.; Bhoj, E. J.; Verheij, J. B.G.M.; Wassink-Ruiter, J. S.Klein; Reis, André; Deshpande, C.; Gregor, Anne; Hill-Karfe, K.; Silfhout, A. T.Vulto van; Pfundt, R.; Bongers, E. M.H.F.; Hakonarson, H.; et al. (Genetics in Medicine, 2020)
Purpose: MED12 is a subunit of the Mediator multiprotein complex with a central role in RNA polymerase II transcription and regulation of cell growth, development, and differentiation. This might underlie the variable phenotypes in males carrying missense variants in MED12, including X-linked recessive Ohdo, Lujan, and FG syndromes. Methods: By international matchmaking we assembled variant and clinical data on 18 females presenting with variable neurodevelopmental disorders (NDDs) and harboring de novo variants in MED12. Results: Five nonsense variants clustered in the C-terminal region, two splice variants were found in the same exon 8 splice acceptor site, and 11 missense variants were distributed over the gene/protein. Protein truncating variants were associated with a severe, syndromic phenotype consisting of intellectual disability (ID), facial dysmorphism, short stature, skeletal abnormalities, feeding difficulties, and variable other abnormalities. De novo missense variants were associated with a less specific, but homogeneous phenotype including severe ID, autistic features, limited speech and variable other anomalies, overlapping both with females with truncating variants as well as males with missense variants. Conclusion: We establish de novo truncating variants in MED12 as causative for a distinct NDD and de novo missense variants as causative for a severe, less specific NDD in females.
CRIS-Team Scopus Importer:2020-12-04